Effect of pH on Microbial Growth and Performance of Paint Produced Using Gum Arabic as a Binder - Mshelia, Yusuf Madu; Lawan, Muhammad Zannah; Lawan, Daggash Muhammad; Sulum, Al-amin Modu (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study investigates the use of gum Arabic as a natural binder in emulsion paint, with particular focus on the influence of pH levels on its physical properties and microbial resistance. Paint formulations were adjusted to pH values ranging from 7.11 to 11.16. Results showed that increasing pH reduced paint density and viscosity, while drying time, scrub resistance, and coverage remained largely unaffected. Microbiological analysis revealed significant bacterial growth, including Bacillus, Pseudomonas, and Staphylococcus species at pH 7.11, whereas no microbial activity was observed at higher pH levels, indicating that pH regulation plays a critical role in minimizing microbial contamination. These findings highlight gum Arabic’s potential as an eco-friendly and sustainable alternative to synthetic binders in paint production. However, the study also emphasizes the importance of incorporating complementary preservation strategies, as long-term microbial resistance under varying environmental conditions may require the addition of natural or synthetic preservatives or synergistic use of other natural compounds. Overall, gum Arabic offers promise for greener industrial applications when coupled with optimized pH control and preservation measures.